2022
DOI: 10.3390/cancers14235862
|View full text |Cite
|
Sign up to set email alerts
|

circRNF10 Regulates Tumorigenic Properties and Natural Killer Cell-Mediated Cytotoxicity against Breast Cancer through the miR-934/PTEN/PI3k-Akt Axis

Abstract: Circular RNA (circRNA), a type of non-coding RNA, has received a great deal of attention with regard to the initiation and progression of tumors. However, the molecular mechanism and function of circRNAs in breast cancer (BC) remain unclear. In the current study, we discovered that hsa_circ_0028899 (also called circRNF10) was significantly reduced in BC tissues, and a higher level of circRNF10 was markedly related to a favorable prognosis. The results of CCK8, colony formation, Transwell, ELISA, and NK cell-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…As for the biological function of circRNF10 in BC, we discovered that circRNF10 inhibited BC proliferation and progression. These findings were consistent with previous studies, which showed that circRNF10 inhibited tumorigenicity by sponging miR-934 and miR-942-5p in BC [ 15 , 16 ]. Considering the inhibitory effect of circRNF10 on BC, it raised the possibility that circRNF10 might become an agent for BC treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As for the biological function of circRNF10 in BC, we discovered that circRNF10 inhibited BC proliferation and progression. These findings were consistent with previous studies, which showed that circRNF10 inhibited tumorigenicity by sponging miR-934 and miR-942-5p in BC [ 15 , 16 ]. Considering the inhibitory effect of circRNF10 on BC, it raised the possibility that circRNF10 might become an agent for BC treatment.…”
Section: Discussionsupporting
confidence: 93%
“…As for the cytoplasmic circRNAs, they mostly acted as a sponge of miRNAs [ 34 ] and decoys of proteins [ 35 ]. Previous studies have explored the role of circRNF10 as an miRNA sponge [ 15 , 16 ]. Differing from these studies, we focused on the potential of circRNF10 in binding proteins and discovered a novel role in which it could bind to DHX15 in BC by interacting with the RecA2 domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to growing data, the majority of circRNAs have a role in the development of BC by acting as miRNA sponges. CircRNF10, for instance, may prevent the progression of BC by sponging miR-934 and controlling the PTEN/PI3K/AKT axis [ 14 ]. Similarly, circ-TRIO could sponge miR-432-5p to regulate the expression of Coiled-Coil Domain Containing 58 (CCDC58) and participate in triple negative BC tumorigenesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%